1972
DOI: 10.1007/bf02609233
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the observed distribution of aflatoxin in shelled peanuts to the negative binomial distribution

Abstract: Suitability of the negative binomial distribution for use in estimating the probabilities associated with sampling lots of shelled peanuts for aflatoxin analysis has been studied. Large samples, called "minilots," were drawn from 29 lots of shelled peanuts contaminated with aflatoxin. These minilots were subdivided into ca. 12 lb samples which were analyzed for aflatoxin. The mean and variance of these aflatoxin determinations for each minilot were determined. The shape parameter k and the mean aflatoxin conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

1980
1980
2011
2011

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(25 citation statements)
references
References 6 publications
1
24
0
Order By: Relevance
“…While it cannot be shown in Table I, the skewness is greater for small sample sizes and the aflatoxin distribution among replicated samples taken from the same lot becomes more symmetrical as sample size increases (Whitaker et al 1972). The above characteristics described by Table I for aflatoxin in raw shelled peanuts are also generally found for other mycotoxins and other commodities (Whitaker et al 1993(Whitaker et al , 1998.…”
Section: Lotmentioning
confidence: 93%
See 1 more Smart Citation
“…While it cannot be shown in Table I, the skewness is greater for small sample sizes and the aflatoxin distribution among replicated samples taken from the same lot becomes more symmetrical as sample size increases (Whitaker et al 1972). The above characteristics described by Table I for aflatoxin in raw shelled peanuts are also generally found for other mycotoxins and other commodities (Whitaker et al 1993(Whitaker et al , 1998.…”
Section: Lotmentioning
confidence: 93%
“…Because of these uncertainties, the true mycotoxin concentration in the lot cannot be determined with 100% certainty by measuring the mycotoxin concentration in a test sample taken from the lot. For example, ten aflatoxin test results associated with taking ten replicated test samples from each of six contaminated shelled peanut lots are shown in Table I (Whitaker et al 1972). For each test result in Table I, the mycotoxin test procedure consisted of the following aspects:…”
Section: Uncertaintymentioning
confidence: 99%
“…Most of the published statistically designed plans have come from the efforts of the group from North Carolina State University and their colleagues (13,14,15,16). They choose to use the negative binomial distribution because it was found that the distribution of aflatoxin contaminated peanuts resembled the distribution of the incidence of contagious diseases (17) which have been described by this statistic.…”
Section: Associated Errorsmentioning
confidence: 99%
“…The problem of sampling shelled peanuts for aflatoxin analysis has been intensely investigated and discussed by Whitaker et al (10,11,12,13,14 e 15). Whitaker et al (10) reported that the distribution of aflatoxin in a lot of shelled peanuts could be quantitatively represented by the negative binomial function.…”
Section: Introductionmentioning
confidence: 99%